Beyond bariatric surgery and weight loss medicaments. A systematic review of the current practice in obesity rehabilitative inpatient programs in adults and pediatrics - Spadaccini, Daniele; Guazzotti, Silvia; Goncalves Correia, Filipa Patricia; Daffara, Tommaso; Tini, Sabrina; Antonioli, Alessandro; Aimaretti, Gianluca; Marzullo, Paolo; Caputo, Marina; Antoniotti, Valentina; Prodam, Flavia (Frontiers in Nutrition, 2022)
Background: Obesity treatment strategies mainly include outpatient lifestyle modification, drugs and bariatric surgery. Voluntary rehabilitative inpatient programs are gaining relevance as potential alternative settings of care that focus on weight loss and prevention of weight regain through a multidisciplinary approach, but their prevalence is still limited due to the high costs. Aim: Considering the lack of evidence in this area, the objective of this study is to systematically review the currently available literature on non-pharmacological and non-surgical inpatient programs aimed at weight loss, to clarify the efficacy and the characteristics of these interventions. Methods: Proper English language articles from 2000 to 2022 were searched on relevant databases. Quality assessment was performed by two different authors using ROB2 and robvis tools. Adult and pediatric studies were reviewed separately and their characteristics were systematically displayed. Results: 36 articles were included (20 on adults, 16 on children and adolescents) for a total of 5510 individuals. The multidisciplinary approach was mainly comprehensive of a low-calorie diet, scheduled physical activity and psychological support based on behavioral treatment. Educational and cooking sessions were present at a lower rate. Globally, inpatient weight loss programs showed a consistent efficacy in reducing body weight and inducing beneficial effects on quality of life, psychological well-being, eating behavior, physical performance and fatigue. Follow-up data were scarce, but with a high percentage of patients regaining weight after a short period. Conclusions: Weight loss inpatient rehabilitation is a promising area that has evidence of all-rounded success in the amelioration of several aspects related to obesity. Nevertheless, it appears to be quite inconsistent in preserving these benefits after the intervention. This might slow the innovation process in this area and preclude further investments from national healthcare. Personalized and enriched programs could show greater impact when focusing on the behavioral and educational aspects, which are crucial points, in particular in pediatrics, for setting up a long-lasting lifestyle modification. More studies are therefore necessary to evaluate long-term efficacy based on the different work-up models,